Antioxidant Activity of Essential Oils Extracted from Aloysia triphylla and Minthostachys mollis that Improve the Oxidative Stability of Sunflower Oil under Accelerated Storage Conditions - Olmedo, Rubén Horacio (2018)
This research determined the antioxidant properties of the essential oils from Aloysia triphylla (AT) and Minthostachys mollis (MM), their antioxidant activity in sunflower oil during accelerated storage (60 °C), and how this storage condition affected the volatiles profile of these essential oils. The main constituents of AT essential oil were neral (27.3%), spathulenol (25.6%), and geranial (24.4%), whereas pulegone (53%) and menthone (29.5%) predominated in MM. Both essential oils presented minor modifications in the chemical compositions after storage at 60 ºC for 14 days. The antioxidant activity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and monitoring the chemical and volatile oxidation indicators during accelerated storage of sunflower oil. The DPPH results showed 48.2 and 24.6%free radical inhibition for AT and MM, respectively. In the accelerated oxidation test, the samples with 0.02% essential oil showed the best antioxidant properties and were comparable to butylated hydroxytoluene. Based on these results, AT and MM essential oils show potential use as antioxidants in foods with high lipid content.